Non-medical aspects of palliative care. Hospice activities in the opinion of different social groups - Flakus, Joanna (Medycyna Paliatywna/Palliative Medicine, 2009)
This study attempted to answer the question whether, and to what extent, the hospice as an institution is fulfilling its aims and tasks regarding social support to the patient and his/her family. The development of hospice care helped to focus attention on the sick person as a subject of care. The medical approach to the problems of the end of life is filled with multimodality and differences. On the one hand, modern medicine is able to prolong life, which is a positive factor. On the other hand, the development of medical procedures brings about new ethical problems and dilemmas. Due to changes in patients’ perception of needs, once again problems of death and dying have become a part of humanistic medicine. In this study the opinions of people outside hospice care about their imagination of that care, and the hospice as an institution, are summarized. Most of these opinions were positive. Knowledge of hospice care facilities and resources in specific cities and towns is correlated with educational activities, especially promotion of voluntary work. Moreover, hospice activities have broadened the community awareness of terminally ill people’s needs and problems and helped to build a special relationship between sick and healthy individuals. The need to be helpful for dying persons leads caregivers to knowledge about the possibilities of hospice care. Last but not least is the fact that hospice care is fully reimbursed.